Stunting Prevention through Cadre Guidance on Early Detection of Toddler Growth and Development with The SDIDTK Application in Malingping – Banten - Rena Mailani; Sri Gunda Fahriana Fahrudin; Sri Yani; Indah Permatasari; Raufina Riandhani Mulyoto; Andini Azzahra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Background: Stunting reduction programs are ongoing in every region in Indonesia, as part of the effort to achieve Indonesia Emas 2045. Good growth supports healthy development. Children who experience stunting will experience developmental disorders. Other factors that influence child development are the environment, parenting styles, and appropriate stimulation from an early age. Early screening can prevent developmental disorders or more severe disabilities. Stunting prevention is carried out through various methods, including basic training in early detection of growth and development and appropriate stimulation to address challenges. Integrated health post (Posyandu) cadres, as the frontline providers of services for infants and toddlers, need to be trained in early detection of growth and development using a simple and fast tool, the Android-based SDIDTK application. The Android-based SDIDTK application is a simple, fast, and accessible instrument for measuring growth and development, available anywhere and anytime. The interpretation of the results obtained in the Android-based SDIDTK application is easy to understand so it is hoped that everyone can apply it, including Posyandu cadres in Malingping sub-district, Lebak – Banten. Objectives: Contribute to preventing stunting by early detection of toddler growth and development. Methods: This community service was implemented using the counseling and mentoring method. Results: The community service are in the form of increased understanding, skills and roles of the Malingping District community, Lebak - Banten regarding early detection of toddler growth and development. Conclusions: The program was conducted as expected and received a positive feedback from the community.